From Value to Uneven Development : Selected Writings by John Weeks in the Marxist Tradition - Fine, Ben, (Historical Materialism Book Series ;, 2024)
John Weeks (1941-2020) was one of the most prominent Marxist economists of his generation. His writings inspired many activists and socialist economists around the world. This book brings together a selection of his writings engaging with and de